Impact Internal Control on Efficiency of the Organizations in Jaffna District - Muraleetharan, P. (Macrothink Institute, 2019)
This study was undertaken with the objective of finding Impact of Internal control on efficiency of organizations in Jaffna District. The study is based on twenty five organizations and wo hundred and forty four respondent in Jaffna District, which are private and public organizations in the district. Internal control assessment is measured by control environment, risk assessment; information and communication, control activities, and monitoring and financial performance is measured by efficiency. Internal control and efficiency measured by correlation analysis and regression analysis. The study finds internal control and efficiency are statistically significant in determining efficiency. Further the study suggests that work performed by the organizations have been implemented in the past and the work schedules take into consideration the goals of internal control. The study further points out that keen attention should be paid on to adopt efficient management information system and training of the staff. All these enhance the staff productivity and reducing costs and also ensure the efficient operation of the firms and financial performance of their operation as well.
Keywords: Efficiency; Internal control; Risk assessment and monitoring